Cycloaddition of N-sulfonyl and N-sulfamoyl azides with alkynes in aqueous media for the selective synthesis of 1,2,3-triazoles - Thumpati, Prasanth (Green Chem, 2022)
The cycloaddition of N-sulfonyl and N-sulfamoyl azides with terminal alkynes generally produces amide derivatives via ketenimine intermediates. We herein delineate a Cu(I) catalyzed method using a prolinamide ligand that selectively generate N-sulfonyl and sulfamoyltriazoles in aqueous media by inhibiting the cleavage of the N(1)-N(2) bond of 5-cuprated triazole intermediates. The present method is mild and tolerant to air, moisture and a wide range of functional groups thereby providing an easy access to a variety of triazole products.